Use of bacteriophages to control membrane biofouling - Tan, Jian Hao (2016)
In this FYP study, the use of bacteriophages as possible biological agent for membrane biofouling control was investigated. Ten bacterial strains were isolated from raw wastewater from Ulu Pandan Water Reclamation Plant, Singapore. The culturing experiment and double layer plaque assay results showed that the isolated phage from the raw wastewater could inhibit the growth of a few species of isolated bacteria by either lytic cycle or temperate cycle. On the other hand, Pseudomonas Aeruginosa PAO1 as model bacteria was also used in this study. The isolated phage significantly limited the growth of PAO1. The inhibition efficiency of the isolated phage was associated with the ratio of phage to bacteria. The effect of the phage on PAO1 membrane biofouling was performed in a bench-scale membrane filtration system. The experimental results showed that the presence of the phage facilitated to alleviate membrane biofouling by reducing biofilm formation on the membrane surface at a lower flux. However, with increasing permeate flux, the benefits from bacteriophages tended to be negligible. The microscopic and SEM images indicated that the presence of the phage in the filtration process appeared to influence biofouling layer morphologies. Less bacterial cells and more EPS were observed in the biofouling layer formed in the presence of the phage. In addition, the filtration experimental results revealed that the ratio of phage and bacteria could determine alleviation efficiency of membrane fouling by the phage.